Study of cardiovascular risk in type 2 diabetic patients in the acute phase of the coronavirus infection and post-COVID period on the background of therapy with sodium-glucose cotransporter-2 inhibitors - N.M. Kushnarоva; O.V. Zinych; A.A. Shuprovych; K.P. Komisarenko (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. The relevance of finding optimal methods for treatment of people with type 2 diabetes (T2DM) who had coronavirus disease 2019 (COVID-19) is due to the fact that these conditions have a number of common pathogenetic mechanisms that cause complications of both diseases. The purpose of the study was to assess the effect of antidiabetic therapy using sodium-glucose cotransporter-2 inhibitors (SGLT2i) on serum level of cardiovascular markers, ST2 peptide and homocysteine, in patients with T2DM in the post-COVID period compared to standard therapy (metformin/sulfonylurea derivatives). Materials and methods. Forty-three T2DM patients aged 44–85 were examined during the acute period of COVID-19 and nine months after recovery. Group 1 (n = 25) received treatment with SGLT2i in addition to metformin; group 2 (n = 18) continued taking a combination of metformin and sulfonylurea derivatives. Group 3 (control) consisted of 32 people without an impaired carbohydrate metabolism who have had COVID-19. The follow-up period was 9–12 months after recovery from COVID-19. Results. In 9 months of treatment, a significant decrease was noted in serum level of homocysteine, which was elevated in the acute period of COVID-19 and reached normal values: in group 1, from 16.8 to 9.9; in group 2, from 14.4 to 10.1 μmol/l; p < 0.05. In addition, in the post-COVID period, there was a significant decrease in the serum level of ST2, the biomarker of cardiovascular pathology, in patients of group 1 (from 5.4 to 4.8 ng/ml; p < 0.05), in contrast to group 2, where ST2 increased (from 4.9 to 5.7; p < 0.05). Patients of group 3, unlike individuals with T2DM from both groups, had a significantly lower average level of ST2 (p < 0.05), which did not change 9 months after the coronavirus infection (p > 0.05). Conclusions. The results obtained confirm the positive effect of taking SGLT2i on the level of cardiovascular risk markers in patients with T2DM who had received gliflozin therapy for 9 months after recovery from COVID-19, in contrast to the group of patients who received metformin/sulfonylurea derivatives.